Alleviation of soil acidity and aluminum toxicity in ultisol using biochar for maize cultivation - Rabileh, Mahamoud Abdillahi (2014)
Phytotoxicity of Al ion (Al3+) and low pH stress are the main two important factors limiting maize production under tropical acid soils in Malaysia. Acid soils in Malaysia are often acidic, account about 72% of the country that was classified under Ultisols and Oxisols. Maize production under these highly weathered soils is not favourable due to aluminium (Al), and manganese (Mn) toxicities accompanied by calcium (Ca) and magnesium (Mg) deficiencies. Al is the main component that contributes to soil acidity. Al saturation in an Ultisol is high (> 60%), which limits maize growth. High Al concentration in acid soils restricts root growth by inhibiting cell elongation and cell division and subsequently reduce crop yield. The addition of biochar to agricultural soils has recently received much attention due to the apparent benefits to correct soil acidity. Studies were carried out to investigate the effectiveness of biochar and ground magnesium limestone (GML) as acid soil ameliorants. Three experiments were conducted: experiment 1) and 2) were carried out in the laboratory, while experiment 3) was conducted in a glasshouse. The first experiment, conducted in the laboratory, was to investigate the effects of different concentration of Al and/or pH on maize root seedling growth and organic acid release. The result showed that increasing Al concentration in the solution had significantly decreased the root length and root surface area; similarly, low pH decreased both root length and root surface area. It was found that root of maize seedling released oxalic acid when exposed to high concentrations of Al and low pH values; however, it can to some extent reduced the effects of Al3+ toxicity by secreting this organic acids. Al concentration and pH value, corresponding to 90 % relative root growth of maize seedling were 20 μM and 6, respectively. The second study was also conducted in the laboratory in batch adsorption experiment. The aim of this experiment was to examine the ability of EFB-biochar for the removal of Al from aqueous solutions. The effects of pH, contact time, adsorbent dosage and initial Al concentration on the adsorption process were investigated. The optimum pH for adsorption was found to be 4. Adsorption of Al ion reached its equilibrium concentration at highest removal percentage within 120 minutes of contact time. The experiments also showed that the highest removal rate was 80% at solution pH 4, contact time 120 minutes and initial concentration of 10 mg L-1 when adsorbent dose was 5 g L-1. The results generally showed that EFB-biochar could be considered as a potential adsorbent for Al removal from aqueous solutions. The third experiment was conducted in a glasshouse to determine the effects of empty fruit bunch based-biochar and/or ground magnesium limestone (GML) on the soil chemical properties and the growth of maize. Biochar was applied at 0, 5, 10 and 20 t ha-1 either in the absence or presence of 2 t GML ha-1. Maize was planted as a test crop. The experiment was arranged in complete randomized block design with four replications. At the end of experiment (50 days), the soil solution in the poly bags was sampled using rhizon soil moisture sampler. Agronomic observations were determined, including height, root growth, dry matter weight (root, leaf and shoot) and nutrient concentration in the maize tissues. The results showed that soil pH, exchangeable bases, basic cations in soil solution, CEC,total C were increased with increasing rate of biochar and/or GML application. It was also found that biochar application had alleviated soil acidity. Applying biochar at the rate of 10 t ha-1 increased soil solution pH from 4.32 to 5.17. The increase in pH was due to the alkalinity existing in the EFB-biochar. Soils treated at this rate of biochar have less Al3+ activities resulting from Al being complexed by the EFB-biochar and/or precipitation of Al as Al-hydroxides when soil pH increased, rendering it inactive and therefore unavailable to the maize. Application of biochar alone or in combination with GML had significantly improved maize growth, shown by the increase in maize height, dry matter weight of roots and shoots. However, biochar application in combination with GML is not cost-effective and farmers cannot afford. Relative maize dry matter weight increased linearly with increasing soil solution pH, while it decreased as Al3+ and Mn2+ activities increased. This study showed that the critical Al3+ activity for maize grown on an Ultisol under tropical condition was 11 μM (about 22 μM in terms of concentration). A good crop of maize can be grown on Ultisols in Malaysia provided that the adverse effects of soil acidity are alleviated. This can be achieved by EFB-biochar applied at 5-10 t ha-1.